Latent heat storage in PCM containing mortars-Study of microstructural modifications - Lucas, S. S.
The incorporation of phase change materials (PCM) into traditional mortars give to these products the ability to store and release heat. In this way it is possible to reduce the energy consumption and improve the thermal comfort in buildings. The introduction of micro and nanomaterials in the mortars matrix can cause microstructural changes that need to be addressed in order to optimize the PCM addition. The relationship between the hardened state performance of different PCM-mortars, its internal microstructure and pore distribution as been observed for different binders such as lime, cement and gypsum. Their hardened state properties, microstructural modifications and heat storage capabilities were evaluated. The ability to store and release heat depends strongly on the size and distribution of internal pores and not only on the PCM content. Using a thermal efficiency test, an important correlation between thermal performance and the mortars microstructure was established, for mortars with 0-30% of PCM added. (C) 2013 Elsevier B.V. All rights reserved.